2019
DOI: 10.1002/app.47961
|View full text |Cite
|
Sign up to set email alerts
|

Divinyl‐terminated polysiloxane as an effective polyacrylates modifier for pigment printing: A study with different molecular weights and quantities

Abstract: Polyacrylates binder is used as an environmental approach for pigment printing. However, the poor water resistance and abrasive resistance of it makes this technique limited. In this study, divinyl‐terminated polysiloxane (Divi‐PDMS) had been used to modify polyacrylates by miniemulsion polymerization. The conversion and coagulation of miniemulsion polymerization were evaluated by gravimetry method, the colloid properties of prepared latexes were obtained and the structures were confirmed by Fourier transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…After the incorporation of ViFS, both of the two copolymers ViFSPA0 and ViFSPA2 had only one T g , suggesting the absence of homopolymer of ViFS. Furthermore, the T g s of the two copolymers were slightly lower than that of PA (−9.1°C), which implied that ViFS segments in the chains increased the flexibility of binder 49 …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…After the incorporation of ViFS, both of the two copolymers ViFSPA0 and ViFSPA2 had only one T g , suggesting the absence of homopolymer of ViFS. Furthermore, the T g s of the two copolymers were slightly lower than that of PA (−9.1°C), which implied that ViFS segments in the chains increased the flexibility of binder 49 …”
Section: Resultsmentioning
confidence: 87%
“…The ViFSPA binders were prepared via mini‐emulsion polymerization according to our previous reports 38,49 . The synthesis route of ViFSPA was shown in Scheme 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, with increasing content of ViPDMS, more polysiloxane segment would migrate onto fabric surface, resulting in lower friction coefficient. 40,41 As a result, the rubbing fastness was also enhanced. When ViPDMS content increased from 0 to 30 wt%, the rubbing fastness of printed fabric raised at least two levels.…”
Section: Characterizationmentioning
confidence: 99%
“…Also, silicone components are introduced into hybrid copolymer materials due to very specific properties of polysiloxane, such as the extremely low T g (−123℃), low surface tension and surface energy, and high thermal resistance. [22][23][24] However, it is also noteworthy that the main problem in the incorporation of silicone into an organic polymer system is the low compatibility with organic polymers. 25 For example, Chen et al 26,27 found that fabrics printed with vinyl polydimethyl siloxane (ViPDMS)-modified PAcr/pigment composite particles possessed lower K/S in a comparted PAcr/pigment system, resulting from the phase separation between PDMS and PAcr.…”
Section: Introductionmentioning
confidence: 99%